Effect of coconut shell ash substitution on compressive strength, wear resistance and water absorption in paving blocks - Khairul Nur Ihfansyah; Mochamad Teguh (Teknisia, 2024)
Waste refers to leftover material generated from production processes, industrial activities, or other human activities, often considered discarded due to its lack of economic value. Coconut shell waste is one such material that has not been optimally utilized, and it often accumulates without adequate disposal. However, coconut shell ash, which contains silica, can potentially enhance the compressive strength of paving blocks. This study investigates the effect of coconut shell ash substitution on the compressive strength, wear resistance, and water absorption of paving blocks. The tests were conducted in accordance with SNI-03-0691-1996 standards, including compressive strength, wear resistance, and water absorption tests. Coconut shell ash was substituted at percentages of 5.5%, 7.5%, 9.5%, 11.5%, and 13.5% by weight of cement. The paving blocks were tested at 28 days. The mixture used a 1:3 ratio of cement to sand, with the sand comprising equal parts Merapi and Progo River sand to balance their different grain characteristics—Merapi sand being angular and sharp, and Progo River sand being fine and round. The compressive strength, wear resistance, and water absorption of normal paving blocks were found to be 36.925 MPa, 0.085 mm/min, and 2.132%, respectively. The highest optimal performance was achieved at 9.5% coconut shell ash substitution, yielding a compressive strength of 40.450 MPa, wear resistance of 0.086 mm/min, and water absorption of 2.349%, meeting the quality category A standard for roads.